MODERN PEDAGOGICAL TECHNOLOGIES IN ENGLISH LESSONS - Bobokulova Shakhnoza Bahriddinovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article highlights the importance attached to foreign languages ​​in the Republic of Uzbekistan and the innovative technologies needed to study them.